Determination of Lead Ion by a Modified Carbon Paste Electrode Based on Multi-Walled Carbon Nanotubes (MWCNTs) and Ligand (N-(4-Hydroxyphenyl) Ethanamide) - Marzieh Bagheri; Amirreaza Talaiekhozani*; Fatemeh Ahmadvand3 (Iranian Journal of Health, Safety and Environment, 2015)
The preparation of a new modified carbon paste electrode (CPE) to measure lead ion has been reported in this study. Lead is a highly toxic element which can have a negative impact on the environment. Therefore, measurement of lead in aquatic environments is very important. Although several methods have been developed for determination of lead ion in aquatic environments, there is no a cheap, simple, accurate and rapid method to measure this ion. Aim of this study is to develop a new method to measure the lead based on using multi walls carbon nanotubes (MWCNTs) and Paracetamol as an ionophore for modification of a CPE. The optimum composition of modified CPE was determined as 64% of graphite powder, 20% of paraffin oil, 12% of nanotube and 4% of ionophore. This optimum composition was shown high selectivity, with appropriate Nernestian slope (-29.73 mV/decade), linear range (from 1.0×10-1to 1.0×10-8M), low lead concentration detection limit (7.5×10-9M) and good response time (equal of 25 sec).The results of this study to introduce a cheap, accurate and simple method for determination of lead ion in aquatic environments.